Revisiting andalusian garden: visions for contemporary Islamic garden design - Abdul Latiff, Zainab; Mohd. Yaman, Maheran (Malaysian Institute Of Planners, 2017)
Andalusian garden is one of the historical gardens in the Muslim world. It appears that the garden designers at the time managed to emulate the spiritual and sacred essence of the paradisiacal environment on earth. The method of content analysis and library search was applied in this study. The findings of this study reveal that the Andalusian garden has been built in accordance with Islamic principles of environment and has crystallized the Quranic paradise description in reality. To conclude, the physical attributes of the Andalusian garden made an essential reference for a contemporary Islamic garden design.